Exploring the potential utility of a mindfulness-based intervention for promoting intuitive eating in adolescents - Cutler, Addie K., author; Shomaker, Lauren, advisor; Lucas-Thompson, Rachel, committee member; Mueller, Megan, committee member (Colorado State University. Libraries, 2022)
Metabolic diseases and other illnesses related to high weight are increasing in prevalence, which is of particular concern in adolescent populations due to the long-term health implications. Intuitive eating (IE), the ability to eat when hungry, stop when satisfied, and consume the foods that one prefers, has been inversely associated with body mass index (BMI; kg/m2) and, as such, is a construct of interest in the field of adolescent wellness. In theory, adolescent IE would be related to both greater mindfulness and less disordered eating. Yet, relatively few studies have examined IE in adolescents and even fewer studies have explored whether mindfulness-based intervention affect IE in adolescents. In this master's thesis, I explored the effects of a mindfulness-based intervention on increasing dispositional mindfulness and increasing IE in adolescents at risk for excess weight gain using baseline and 3-year follow-up data from a pilot randomized controlled trial of N=54 adolescent girls (55%) and boys 12-17 years old who were experiencing above-average weight or had a family history of experiences with obesity. Youth were randomized to either a mindfulness-based group intervention or health education control group for 6 hours spread over 6 consecutive weeks. Mindfulness and disordered eating were measured on validated self-report instruments at baseline and 3-year follow-up. IE was measured through adolescents' report on the Intuitive Eating Scale-2, measured only at 3-year follow-up. There were no significant differences between groups in mindfulness, disordered eating, or IE at 3-year follow-up. Disordered eating at 3-year follow-up was negatively correlated with total average IE at 3-year follow-up. These findings are limited based on the small, pilot nature of the study indicating that further research is needed in this area.
Keywords: eating behaviors; mindfulness; intuitive eating; adolescent